Datação de Cerâmicas Arqueológicas do Noroeste Paulista pelo Método da Termoluminescência - Umiji, Reinaldo Massayuki [UNESP] (2014)
The insertion of the physical sciences has provided great contribution to archaeology with the most distinct studies dating techniques, allowing all kinds of materials can be found dated and consequently establish the relationship between cultures and their chronology. The thermoluminescence dating technique considers that pottery materials have in their composition thermoluminescent crystals that were exposed to ionizing radiation, due to the presence of cosmic rays and radionuclides, which accumulate this energy in the so called metastable levels, and when heated thermoluminescence intensity emitted by the sample is proportional to the time that it has been exposed to the radiation. Thus, the present study deals with the absolute dating of ceramic fragments from the Archaeological Sites Aguinha, Célia Maria, Pernilongo, Ragil, Turvo III and V, by applying dating by Thermoluminescence (TL). As a consequence, this study well provide subsidies to establish a chronology for archaeological occupations, comparing the present results with dating already performed. Comparing the results obtained in this work, we observe that already carried the fragment Site Ragil, results showed that neither confirms archaeological interpretation. However the remaining fragments allowed even confirm the time of occupation